2008
DOI: 10.3858/emm.2008.40.5.479
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 inhibits the degradation of HIF-1α by pVHL-mediated ubiquitination

Abstract: Abbreviations: HIF-1α, hypoxia inducible factor-1α; STAT3, signal transducer and activator of transcription 3; VHL, von Hippel-Lindau Abstract Hypoxia-inducible factor 1α (HIF-1α) is rapidly degraded by the ubiquitin-proteasome pathway under normoxic conditions. Ubiquitination of HIF-1α is mediated by interaction with von Hippel-Lindau tumor suppressor protein (pVHL). In our previous report, we found that hypoxia-induced active signal transducer and activator of transcription3 (STAT3) accelerated the accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 23 publications
9
88
0
Order By: Relevance
“…Although STAT3 is known as a transcriptional factor, STAT3-mediated regulation of MGMT did not depend on its transcriptional activity. Recently, it has been reported that active STAT3 is involved in protein stabilization through inhibition of the ubiquitylation of the target molecule (41), and consistent with this report, we observed that MGMT downregulation by STAT3 inhibitor was recovered partially by the proteasome inhibitor MG132 treatment. However, it should be noted that ubiquitylated levels of MGMT were unchanged after STAT3 inhibitor treatment (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…Although STAT3 is known as a transcriptional factor, STAT3-mediated regulation of MGMT did not depend on its transcriptional activity. Recently, it has been reported that active STAT3 is involved in protein stabilization through inhibition of the ubiquitylation of the target molecule (41), and consistent with this report, we observed that MGMT downregulation by STAT3 inhibitor was recovered partially by the proteasome inhibitor MG132 treatment. However, it should be noted that ubiquitylated levels of MGMT were unchanged after STAT3 inhibitor treatment (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…STAT3 has been shown to positively regulate HIF1a expression through transcriptional and posttranscriptional mechanisms (37,38,59). However, we showed that STAT3-deficient TCCs expressed slightly higher levels of HIF1α and its transcriptional targets compared with controls, suggesting a paradoxical role for STAT3 as a negative regulator of HIF1α.…”
Section: Discussionmentioning
confidence: 55%
“…CoCl 2 stabilizes the HIF1α in normoxia, impeding its proteasomaldependent degradation (36). STAT3 has been shown to both transcriptionally regulate HIF1α and impede its degradation through the sequestration of the von Hippel-Lindau tumor suppressor, E3 ubiquitin protein ligase (VHL-E3) (37,38). We observed that CoCl 2 induced HIF1α accumulation at similar levels in both shCT and shSTAT3 cells (Fig.…”
Section: Igfbp7mentioning
confidence: 59%
“…On the one hand, STAT3 transcriptionally upregulates HIF1A; 47 on the other hand, STAT3 interacts with the C-terminal domain of HIF1A and stabilizes the protein from ubiquitination mediated by VHL (von Hippel-Lindau tumor suppressor, E3 ubiquitin protein ligase). 48 Interestingly, HIF1A may also modulate autophagy in a context-dependent manner. HIF is a heterodimer of a constitutive b subunit and an oxygen-regulated a subunit 50 demonstrates that the stable overexpression of HIF1A reverses the induction of autophagy by the JAK2-STAT3 inhibitor cucurbitacin I in U251 cells.…”
Section: Stat3 In Autophagymentioning
confidence: 99%